Novel CTNND2‐TERT fusion in a spindle cell liposarcoma. Issue 9 (6th May 2020) - Occidental, Michael; Shen, Guomiao; Feng, Xiaojun; Zhu, Kelsey; Kelly, Kevin; Nie, Qian; Reddi, Honey V.; Lakiotaki, Eleftheria; Viniou, Nora Athina; Korkolopoulou, Penelope; Linos, Konstantinos; Jour, George
Abstract: Soft tissue tumors can be categorized molecularly into two categories: tumors which are known to have recurrent molecular alterations and tumors which do not have consistent recurrent molecular alterations or translocations. These "nontranslocation" associated sarcomas are clinically more aggressive than their more stable counterparts. However, recent advances in RNA sequencing have discovered recurrent novel fusions within the latter group, namely TERT‐TRIO fusions. Furthermore, a recent report discovered this fusion in a spindle cell liposarcoma. Our case describes a novel fusion of CTNND2, a neighbor gene of TRIO, and TERT in a spindle cell liposarcoma, and provides further evidence that spindle cell liposarcoma should be a distinct entity from dedifferentiated liposarcoma.